ON THE RATIO OF NON-PERFORMING LOANS TO AVERAGE LOAN RATES IN CONSIDERING THE ISSUE OF BANKING RISKS (Journal of Universal Science Research, 2024)
Banking activities are of constant interest from researchers and practitioners. The basis of this interest is the role and importance of banks in the economic activities of various economic agents and the life of the population. At the same time, special attention is paid to banking risks, where we highlight credit risks. Based on this, the paper examines the dynamics of the ratio of non-performing loans to loan rates on average on the banking system for a number of individual countries. Graphs and diagrams of such analysis are provided, which allows you to understand the progress of this study.